Farewell to markets? Barack Obama continues to define his economic agenda - Stormy-Annika Mildner (Stiftung Wissenschaft und Politik (SWP), 2008)
'It's the economy, stupid' - again. The state of the economy, which already helped Bill Clinton win the presidential elections in 1992, once again paved the way to the White House for the Democratic candidate in 2008. But Barack Obama inherits a much more difficult economic legacy. He will be inaugurated at a moment of crisis worse than any economic downturn since the Great Depression of the 1930s. The President-elect therefore believes that the government should renew widespread economic security and create equal opportunities for all citizens, not unlike the Kennedy administration did in its New Economics. His economic plans include health care reform, a green revolution, stricter financial regulation, and a shift of tax burden from the middle class to the rich. The 2008 elections are thus likely to mark the restoration of the activist government. But while Obama clearly opposes Ronald Reagan's anti-government and deregulation philosophy, he will, just as his predecessors, continue to rely on market forces, believing in the importance of market incentives and efficiency
Keywords: 320